Omega‐3 polyunsaturated fatty acid encapsulation system: Physical and oxidative stability, and medical applications. Issue 2 (14th January 2022) - Du, Qiwei; Zhou, Linhui; Li, Minghui; Lyu, Fei; Liu, Jianhua; Ding, Yuting
Abstract: The benefits of omega‐3 (ω‐3) polyunsaturated fatty acids (PUFAs) to human health and the therapeutic properties of diseases have been widely identified. However, due to abundant double bonds, they are sensitive to environmental conditions which cause oxidative deterioration. This is one of the main factors limiting their application. The encapsulation of ω‐3 PUFAs is an effective way to improve their oxidation stability. This review summarizes the recent advances in different forms of ω‐3 encapsulation systems, such as emulsions, liposomes, microcapsules, and liquid crystalline. Particular emphasis is given to the effects of food‐derived biopolymers wall materials (proteins, polysaccharides, and esters) on encapsulation efficiency and oxidation stability of ω‐3 PUFAs encapsulation systems. In addition, the effects of natural antioxidants (polyphenols, carotenoids, flavonoids, plant essential oils, etc.) on the antioxidant enhancement of ω‐3 PUFAs encapsulation system based on food‐derived biopolymers are discussed. Different forms of ω‐3 PUFAs encapsulation systems have been proven to be used as supplements in the medical field. The regulation and improvement of the ω‐3 PUFAs encapsulation system on the diseases of animal and human, which are related to central nervous system, retina, lung, kidney and tissue cell, are systematically discussed. Abstract :